DIGITAL SPACE AND HIDDEN SOCIAL PRACTICES - Ahmad, Busyairi; Irwan, Irwan (Gema Kampus IISIP YAPIS Biak, 2025)
This study explores the use of the MiChat application as a platform for establishing temporary relationships, particularly in the context of searching for one-night stand partners. Using a qualitative approach, this research collects data through in-depth interviews and participatory observation of active MiChat users. The findings reveal that this application functions as a digital space that allows individuals to express emotional and sexual needs without being bound by conventional social norms. MiChat users often create personal justifications for this practice, even though it is considered contrary to prevailing moral values. This study highlights how modern communication technology is transforming social interaction patterns, creating new dynamics that blur the boundaries between public and private spaces. The results of this study contribute significantly to understanding the impact of digital media on social behavior and identity construction in contemporary society.